Sustainable Urban Mobility in the São Paulo State - Pasquotto, Geise Brizotti (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
Resilient cities are those that, exposed to risks, have the ability to resist, absorb, adapt and recover, in a planned and efficient manner. Currently, one of the greatest weaknesses in the world is environment related, therefore, it is urgent to rethink the way cities are developing. In this essay, the issue of air pollution will be addressed, mainly in relation to urban mobility. Based on air quality data and strategic mobility actions, some reflections will be raised taking into account the directed aspects and systemic vision of the process.